2014
DOI: 10.1111/jace.13373
|View full text |Cite
|
Sign up to set email alerts
|

Domain Structure of Potassium‐Sodium Niobate Ceramics Before and After Poling

Abstract: Domain structure and domain wall motion play important roles on the piezoelectric properties of ferroelectric ceramics. In this work, the domain structure of hot‐pressed (K0.50Na0.50)NbO3 (KNN) ceramics before and after poling were studied by observing the domain patterns with an acid‐etching technique, and the extrinsic contribution to the piezoelectric properties were evaluated. It was found that the domain structure of the unpoled KNN ceramic was relatively complicated with many watermark, herringbone and z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 53 publications
(96 reference statements)
1
29
0
Order By: Relevance
“…[40] Previous works have revealed that extrinsic contribution plays an important role in KNN, especially for the compositions near PPT. [41,42] Therefore, it provides us with another easy approach to locating the PPT point T O-T by assessing the temperature and frequency dependence of piezoelectric properties. For a better understanding of the underlying mechanisms of enhanced performance in piezoelectrics, the simple but classical KNbO 3 lead-free piezoelectric is recently highlighted in both theoretical and experimental researches.…”
Section: Resultsmentioning
confidence: 99%
“…[40] Previous works have revealed that extrinsic contribution plays an important role in KNN, especially for the compositions near PPT. [41,42] Therefore, it provides us with another easy approach to locating the PPT point T O-T by assessing the temperature and frequency dependence of piezoelectric properties. For a better understanding of the underlying mechanisms of enhanced performance in piezoelectrics, the simple but classical KNbO 3 lead-free piezoelectric is recently highlighted in both theoretical and experimental researches.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the domain width is influenced by NBT crystal morphologies, which is corresponding to the intensity change in XRD peaks as shown in Figs. (c), (f) and (i) …”
Section: Resultsmentioning
confidence: 93%
“…At present, lead‐based materials are predominant for piezoelectric applications, which imposes severe impacts on the human health and environment . As the most promising candidates to replace the lead‐based ceramics, Na 0.5 Bi 0.5 TiO 3 (NBT), K 0.5 Na 0.5 NbO 3 (KNN), and BaTiO 3 (BT) have attracted growing interest …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In the recently reported domain patterns and structure for potassium sodium niobate (KNN)-based ceramics by scanning electron microscopy (SEM), the domain patterns and a structure transition from a complicated domain structure with many watermark, (a) E=80kV herringbone, and zigzag patterns for unpoled samples to only a single set of parallel domain stripes for poled ceramics due to domain reorientation and domain wall motion, associated with increased average domain size, was observed. 31,32 On the other hand, a characterization method for ferroelectric domains has been proposed by Tan's group, 33 who established the domain structure-dielectric property relationship for BNT-BT ceramics and found that regular ferroelectric domains correspond to minimum room-temperature frequency dispersion in the dielectric constant while nanodomains lead to strong frequency dispersion.…”
Section: Resultsmentioning
confidence: 99%